The Relationship Between Self Efficacy and Social Support with Stress in Students who are Working on Their Final Project (Case Study of Students of Public Health Study Program of Undana FKM) - Patresia Marsela Padamaley; Ribka Limbu; Eryc Z. Haba Bunga; Imelda F. E Manurung (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Higher education in Indonesia is very important to form quality human resources. Students, as the main part of higher education, often face great demands. Because of these various pressures and demands, students are a group that has a high potential for stress. Preparation of the final project is one of the stressors on students in the academic world. Purpose: This study aims to determine the relationship between self efficacy and social support with stress in students of the Public Health Study Program, Faculty of Public Health, Nusa Cendana University who are working on their final project. Methods: The type of research used in this study was an analytical survey with a Cross Sectional research design and the number of samples in this study consisted of 66 students from the class of 2020 who were selected using simple random sampling technique. The data analysis technique uses the Chi-square statistical test with a significance level of ? = 0.05. Results: The results obtained show that there is a relationship between self efficacy (p-value = 0.001) and social support (p-value = 0.000) with the stress of students who are doing their final project. Conclusions: It can be concluded that final year students face various challenges and pressures in the process of preparing their final project, which often lead to significant levels of stress. Factors such as self-efficacy and social support play an important role in influencing academic stress levels. High self-efficacy can help students feel more confident and capable of facing various difficulties, while social support from family, friends, and the surrounding environment can provide a sense of comfort and reduce the emotional burden they feel. Students of the Public Health Study Program of FKM Undana who are working on their final project are advised to increase self-confidence, seek social support, and manage stress through time management, adequate rest, and healthy eating and sleeping patterns. The faculty is expected to provide stress management programs, counseling, and support groups, and improve guidance services. This research can also be used as a reference for further studies on stress in students.